2008
DOI: 10.1063/1.2967875
|View full text |Cite
|
Sign up to set email alerts
|

Unusual catalyst-free epitaxial growth of silicon nanowires by thermal evaporation

Abstract: We report a catalyst-free epitaxial growth of silicon nanowires on polyhedral facets of mother Si nanoparticles by thermal evaporation process. Single silicon nanowires and octopuslike silicon nanowires (OSNWs) were synthesized under different temperatures. The OSNWs have several directions including ⟨112⟩, ⟨110⟩, and the unusual directions of ⟨100⟩ and ⟨111⟩. A catalyst-free temperature-dependent epitaxial growth model was suggested. Using the Wulff theory and first principle calculations, these growth direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…For a crystalline Si NW surrounded by a layer of amorphous SiO x synthesized by laser ablation and thermal evaporation, an oxide-assisted mechanism has been proposed in which a SiO NP is thought to play a key role in the formation of the Si NW and SiO x layer . Crystalline Si NWs were synthesized without adding any catalysts by thermal evaporation and chemical vapor deposition. , The growth of a Si NW on a NP was explained by a vapor–solid (VS) mechanism, in which Si vapor directly deposits on the seed NP to nucleate and grow the NW. The sites for the nucleation and growth of Si NWs are Si–metal alloy NPs, , Si NPs covered with SiO x layers, and Si NPs. , Not all of the sites of grown Si NWs have been identified yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a crystalline Si NW surrounded by a layer of amorphous SiO x synthesized by laser ablation and thermal evaporation, an oxide-assisted mechanism has been proposed in which a SiO NP is thought to play a key role in the formation of the Si NW and SiO x layer . Crystalline Si NWs were synthesized without adding any catalysts by thermal evaporation and chemical vapor deposition. , The growth of a Si NW on a NP was explained by a vapor–solid (VS) mechanism, in which Si vapor directly deposits on the seed NP to nucleate and grow the NW. The sites for the nucleation and growth of Si NWs are Si–metal alloy NPs, , Si NPs covered with SiO x layers, and Si NPs. , Not all of the sites of grown Si NWs have been identified yet.…”
Section: Introductionmentioning
confidence: 99%
“…Crystalline Si NWs were synthesized without adding any catalysts by thermal evaporation and chemical vapor deposition. , The growth of a Si NW on a NP was explained by a vapor–solid (VS) mechanism, in which Si vapor directly deposits on the seed NP to nucleate and grow the NW. The sites for the nucleation and growth of Si NWs are Si–metal alloy NPs, , Si NPs covered with SiO x layers, and Si NPs. , Not all of the sites of grown Si NWs have been identified yet.…”
Section: Introductionmentioning
confidence: 99%
“…With a decrease in sublimation temperature of the SiO source, they observe a strong drop of nanowire yield due to decreased partial pressure of SiO in the Ar carrier gas. Qin et al [16] also report catalyst-free growth of Si nanowires by thermal evaporation of SiO. They used a static reaction chamber instead of a tube with gas flowing through, which probably results in a much higher SiO partial pressure in the gas.…”
Section: Discussionmentioning
confidence: 95%
“…Further dissolution of the silicon induces supersaturation in the particles, and excess silicon solidifies at the catalyst surface. The concept of the VLS mechanism remains valid for a wide range of diameters, from nanometers to hundreds of micrometers, and many studies have reported the successful formation of SiNWs, or wires. However, there are only a few studies in which the in situ observation of wire growth was performed. The existing work includes excellent in situ observations of SiNW growth using transmission electron microscopy and scanning electron micrscopy; using a simpler technique, the direct observation of wire growth using optical microscopy has been reported. , It is not possible to observe the growth of single nanowires using visible light, but optical techniques are still useful for the observation of the growth of silicon wires.…”
Section: Introductionmentioning
confidence: 99%